ANALISIS PELAKSANAAN PEMBELAJARAN METODE RESITASI DALAM JARINGAN OLEH GURU MATA PELAJARAN EKONOMI DI SMK - Agustina Agustina; F.Y. Khosmas; Bambang G.S (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis thesis is entitled “Implementation of Recitation Method Learning in thenetwork by Economics Subject Teachers at SMK Negeri 1 Pontianak. The methodused is descriptive method. The form of the research is qualitative description.Data collection techniques in this study were: direct communication with datacollection tools, interview guides, direct observation with data collection tools,observation sheets, documentary studies with data collection tools, school dataarchives. With the results of the study as follows: 1) Planning for learning therecitation method in the network by a teacher of economics subject at SMK Negeri1 Pontianak. learning the recitation method in the network is in accordance withthe learning syntax. 2) Implementation of online recitation method learning in thenetwork by a teacher of economics subject at SMK Negeri 1 Pontianak. 3)Evaluation of online recitation method learning in the network by a teachers ofeconomics subjects at SMK Negeri 1 Pontianak. In this evaluation, teachers ofeconomics subjects at SMK Negeri 1 Pontianak, evaluated by giving assignmentsonline. This recitation method is used or given to stimulate children to be diligent,diligent, and active in learning, so that when teaching and learning activities theyare ready. In addition, this method is given because it is felt that the lessonmaterial is too much while the time is little, in the sense that the material is a lotbut the time is not balanced. So that the material given can be in accordance withthe available time, this method can be given.Keyword : Implementation of Online Recitation Method Learning, EconomicsSubject Teacher, SMK Negeri 1 Pontianak